The Importance of the Application of Michael Michalko's Concept of Leadership Science in Entrepreneurship Course at University - Purnamasari, Linda; Trysia, Vallyrina (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to explore the application of entrepreneurship based on innovative and creative leadership, according to Michael Michalko, to students of Esa Unggul University. The university's vision, which prioritizes intellectuality, creativity, and entrepreneurship, is expected to produce graduates who can become leaders in the business world. This study uses a qualitative method with data analysis from the work results of the Entrepreneurship 1 course students in the 2020/2021 academic year. The researcher collected data from online and virtual assignments carried out by students during 14 learning sessions. The study results show that innovative leadership-based entrepreneurship helps students develop the potential to think creatively in responding to business challenges, predicting business opportunities, and designing business ideas that others have not thought of. It is proven that Michael Michalko's application of entrepreneurship can provide solutions for students to achieve entrepreneurial independence in the era of global competition.